A EDUCATIONAL MEASURES AS REPRESSIVE MEASURES FOR FIGHTING AND PREVENTING JUVENILE DELINQUENCY IN THE REPUBLIC OF MACEDONIA - Sulejmani, Ersin (International Scientific Journal Vision, 2017)
Juvenile delinquency, as a negative phenomenon, today is an international social problem that every country is faced with, the Republic of Macedonia as well. The process of fighting and preventing juvenile delinquency has a special importance in a society of a country because juveniles are the future of a healthy nation. Thus, without a healthy youth we do not have a healthy society. Crime in general and juvenile crime in particular is an occurrence dependent on many causes and factors, which are also associated with the general socio-economic circumstances of a particular region or even a society. For this reason, specific and adequate measures are to be taken towards this category by the state institutions, nongovernmental institutions but also by the society itself. This phenomenon should be also evaluated in multidimensional terms, since the treatment of crime is a complex phenomenon and in a way related to all human categories, from juveniles to adults as perpetrators of criminal acts. This is because we are dealing with common environments, lifestyle, activity, education, where necessarily, these causes and factors constrain each other.